Grass cell wall feruloylation: distribution of bound ferulate and candidate gene expression in Brachypodium distachyon - Molinari, Hugo B.; Pellny, Till K.; Freeman, Jackie; Shewry, Peter R.; Mitchell, Rowan A. (Frontiers in Plant Science, 2013)
The cell walls of grasses such as wheat, maize, rice, and sugar cane, contain large amounts of ferulate that is ester-linked to the cell wall polysaccharide glucuronoarabinoxylan (GAX). This ferulate is considered to limit the digestibility of polysaccharide in grass biomass as it forms covalent linkages between polysaccharide and lignin components. Candidate genes within a grass-specific clade of the BAHD acyl-coA transferase superfamily have been identified as being responsible for the ester linkage of ferulate to GAX. Manipulation of these BAHD genes may therefore be a biotechnological target for increasing efficiency of conversion of grass biomass into biofuel. Here, we describe the expression of these candidate genes and amounts of bound ferulate from various tissues and developmental stages of the model grass Brachypodium distachyon. BAHD candidate transcripts and significant amounts of bound ferulate were present in every tissue and developmental stage. We hypothesize that BAHD candidate genes similar to the recently described Oryza sativap-coumarate monolignol transferase (OsPMT) gene (PMT sub-clade) are principally responsible for the bound para-coumaric acid (pCA), and that other BAHD candidates (non-PMT sub-clade) are responsible for bound ferulic acid (FA). There were some similarities with between the ratio of expression non-PMT/PMT genes and the ratio of bound FA/pCA between tissue types, compatible with this hypothesis. However, much further work to modify BAHD genes in grasses and to characterize the heterologously expressed proteins is required to demonstrate their function.